(untitled) (Singaporean Journal of Business Economics and Management, 2020)
This seminar work focus on the effect of oil price on Nigeria economic growth. Specifically the study aims at pursuing the following objectives: To determine the extent at which oil price instability affect standard of living, and to ascertain the impact of increase in oil prices and economic growth. The study population comprises of 2248 members of host community, Warri, Delta State. The sample size of 399, using Taro Yamane statistical formula at 5% error of tolerance. Secondary data were used. The total number of 399 copies of the questionnaires was distributed while 320 copies were returned and 79 copies were not returned. Historical research design was adopted for the study. Two hypotheses were tested using Pearson product moment correlation coefficient and simple linear regression tool. The findings indicate that Oil price instability negatively affected standard of living ( r = 0.928 ; F = 1983.45 144.531; p < 0.05 ) There was a negative relationship between increase in oil price and economic growth (r =. 913, P < 0.05 ). The study concluded that oil prices have become so important to the Nigerian economy that principal economic policy makers at the CBN and the Federal Ministry of Finance factor them into economic policy decisions. The study recommends that Nigeria should factor look inwards amidst the abundance of its untapped natural resources to diversify the economy of the nation, and increase export with a view to checkmating the insidious impact of the oil price fall on the economy